An Assessment of Financial Performance and Service Facility Improvement after Merger and Acquisition of Financial Institutions of Nepal - Bajgai, Ganesh; Pradhan, Radheshyam (International Research Journal of MMC, 2021)
Merger and acquisition are one process to integrate the two or more similar types of institutions into one institution. Basically, more banking sectors are gone in merger and acquisition in Nepal. Nepal Rastra Bank has introduced the Merger by law – 2068 BS with the objective of reducing the number of BFIs, enhancing financial stability and promoting public confidence on the banking sector, which encouraged and compelled the banking sectors to proceed the merger and acquisition process for their long-term sustainability. Considering this status, the study was conducted to identify the impact of merger and acquisition on financial performance and service quality of financial institutions of Nepal. The study was conducted covering the category A and B bank which were established after merger and acquisition process. It was a cross-sectional study conducted among the 385 employees of banking sectors. The result shows that the financial performance and service quality of both types of banks (category A and B) was significantly difference in post-merger situation because the p value of t-test was less than .05 significant level.